Functional insights from biophysical study of TREM2 interactions with apoE and Aβ1‐42. Issue 3 (8th October 2020) - Kober, Daniel L.; Stuchell‐Brereton, Melissa D.; Kluender, Colin E.; Dean, Hunter B.; Strickland, Michael R.; Steinberg, Deborah F.; Nelson, Samantha S.; Baban, Berevan; Holtzman, David M.; Frieden, Carl; Alexander‐Brett, Jennifer; Roberson, Erik D.; et al.
Abstract: Introduction: Triggering receptor expressed on myeloid cells‐2 (TREM2) is an immune receptor expressed on microglia that also can become soluble (sTREM2). How TREM2 engages different ligands remains poorly understood. Methods: We used comprehensive biolayer interferometry (BLI) analysis to investigate TREM2 and sTREM2 interactions with apolipoprotein E (apoE) and monomeric amyloid beta (Aβ) (mAβ42). Results: TREM2 engagement of apoE was protein mediated with little effect of lipidation, showing slight affinity differences between isoforms (E4 > E3 > E2). Another family member, TREML2, did not bind apoE. Disease‐linked TREM2 variants within a "basic patch" minimally impact apoE binding. Instead, TREM2 uses a unique hydrophobic surface to bind apoE, which requires the apoE hinge region. TREM2 and sTREM2 directly bind mAβ42 and potently inhibit Aβ42 polymerization, suggesting a potential role for soluble sTREM2 in preventing AD pathogenesis. Discussion: These findings demonstrate that TREM2 has at least two ligand‐binding surfaces that might be therapeutic targets and uncovers a potential function for sTREM2 in directly inhibiting Aβ polymerization.